Low expansion coefficient high borosilicate glass and preparation method thereof

By adding octadecane-coated silica microspheres to the high borosilicate glass to adjust their thermal expansion behavior, the problem of high borosilicate glass with high thermal expansion coefficient is solved, significantly reducing the thermal expansion coefficient and enhancing the thermal shock resistance. Suitable for high temperature application scenarios.

CN118545907BActive Publication Date: 2025-01-14ZIBO INTRUE LIGHT IND PROD CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411016644.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-07-29
Publication Date
2025-01-14
Estimated Expiration
2044-07-29

AI Technical Summary

Technical Problem

The existing high borosilicate glass has relatively high thermal expansion coefficient and is prone to fracture at high temperatures, which cannot meet the application environment with low thermal expansion coefficient requirements.

Method used

Add octadecane-coated silica microspheres to the raw materials of borosilicate glass, and adjust the thermal expansion behavior of the glass through phase change characteristics. Combined with optimized formula and preparation process, it significantly reduces the thermal expansion coefficient of the glass and improves the resistance to cold and heat Impactness.

Benefits of technology

It significantly reduces the thermal expansion coefficient of high borosilicate glass, enhances its thermal stability and thermal shock resistance, extends the service life of the product, and is suitable for application scenarios where temperature sudden changes are required.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The present application belongs to the technical field of high borosilicate glass, and particularly relates to a low expansion coefficient high borosilicate glass and a preparation method. The raw materials of the high borosilicate glass include, by weight: 65-75 parts of silicon dioxide, 20-25 parts of boron oxide, 2-5 parts of zinc oxide, 2-5 parts of sodium oxide, 1.2-2 parts of aluminum oxide, 0.1-0.5 parts of lithium oxide, and 0.2-0.6 parts of silicon dioxide microspheres containing octadecane. After mixing, the raw materials are melted until the raw materials are completely melted to form glass liquid. After clarifying and blowing annealing, the high borosilicate glass is obtained. The obtained high borosilicate glass has a lower expansion coefficient and superior resistance to cold and hot shock, which improves the thermal shock resistance of the material and prolongs the service life.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of high borosilicate glass and in particular to a low expansion coefficient high borosilicate glass and a preparation method thereof. Background Art

[0002] Low expansion coefficient high borosilicate glass is a special type of glass material, known for its excellent physical and chemical properties. Its main features include low thermal expansion coefficient, high temperature resistance, high strength, high hardness and good chemical stability. Its components are silicon oxide and boron oxide. Silicon oxide, as the basic component, provides the basic structure of glass. Boron oxide is a key additive that significantly reduces the thermal expansion coefficient of glass and improves heat resistance and chemical stability. The boron content in high borosilicate glass is usually between 10% and 25%, and also includes oxides such as sodium, potassium, and aluminum. These auxiliary components help to adjust the melting point, viscosity and other properties of the glass. The thermal expansion coefficient of high borosilicate glass is much lower than that of ordinary glass, which makes it less likely to crack when the temperature changes drastically. It has excellent thermal stability, which means that its volume changes very little when the temperature changes, reducing the stress caused by thermal expansion and contraction, thereby enhancing the crack resistance and stability of the glass. High borosilicate glass can withstand extremely high temperatures, reaching more than 1000°C in short-term use, and is suitable for making utensils and equipment that need to withstand extreme temperature changes. High borosilicate glass also has excellent transparency, high light transmittance, good permeability to visible light and some ultraviolet rays, and strong resistance to chemicals such as acids and alkalis. It is suitable for chemical laboratories and the chemical industry. Compared with ordinary glass, high borosilicate glass has higher hardness and strength, and is scratch-resistant and impact-resistant. High borosilicate glass is often used in industries such as laboratory equipment, kitchen supplies, pharmaceutical packaging, solar energy industry, lighting industry, and home appliance components, such as precision instruments, heat-resistant kettles, pharmaceutical packaging materials, packaging materials for photovoltaic modules, reflective cups, etc.

[0003] CN103626395B discloses a method for preparing high borosilicate glass, wherein the raw materials are calculated as oxides, including: 60-75 parts by weight of silicon dioxide, 10-25 parts by weight of boron oxide, 2-6 parts by weight of aluminum oxide, 0-10 parts by weight of alkali metal oxides, 0-5 parts by weight of R oxides and 0.2-0.5 parts by weight of antimony trioxide, wherein R is at least one of zinc, calcium and barium. The raw materials are mixed evenly, and the mixed raw materials are melted into glass liquid using a platinum crucible, and oxygen or liquid oxygen is introduced into the bottom of the glass liquid at a flow rate of 0.5-3L / min for 10-60min using a platinum tube; after standing for 1-2h, the glass liquid is stirred at a speed of 20-100rpm using a frame-type platinum stirrer for 2-5h, and high borosilicate glass is obtained after cooling, forming, annealing and physical polishing. The high borosilicate glass obtained by the technical solution provided in this application has high optical uniformity, but it is still not suitable for application environments with low requirements for thermal expansion coefficient. Summary of the invention

[0004] In order to solve the problem that high borosilicate glass in the prior art has a relatively high thermal expansion coefficient and is easy to break at high temperatures, the present application provides a low expansion coefficient high borosilicate glass and a preparation method, and silica microspheres coated with octadecane are added to the raw materials. The obtained high borosilicate glass has a lower expansion coefficient and excellent resistance to thermal shock.

[0005] The present application provides a method for preparing low expansion coefficient high borosilicate glass, comprising the following steps:

[0006] S1, adding tetraethoxysilane and methyltrimethoxysilane into deionized water, and heating the mixture under stirring to react;

[0007] S2. After the reaction is completed and cooled, octadecane and 3-aminopropyltriethoxysilane are added and mixed evenly, and then polyvinyl alcohol is added to the mixture. After mixing evenly, an aqueous ammonium hydroxide solution is added dropwise, and stirring is continued at room temperature. After filtering, the mixture is washed and dried to obtain microspheres;

[0008] S3. After mixing, the raw materials of high borosilicate glass are melted until the raw materials are completely melted to form glass liquid. After clarifying and blowing annealing, the high borosilicate glass is obtained. The raw materials of the high borosilicate glass include, by weight: 65-75 parts of silicon dioxide, 20-25 parts of boron oxide, 2-5 parts of zinc oxide, 2-5 parts of sodium oxide, 1.2-2 parts of aluminum oxide, 0.1-0.5 parts of lithium oxide, and 0.2-0.6 parts of the microspheres obtained in step S2.

[0009] Furthermore, in step S1, the molar ratio of tetraethoxysilane to methyltrimethoxysilane is 1-1.8:1.

[0010] Furthermore, the mass ratio of octadecane, tetraethoxysilane, 3-aminopropyltriethoxysilane and polyvinyl alcohol is 0.1-0.5:1:0.01-0.04:0.05-0.1.

[0011] Furthermore, the heating temperature in step S1 is 75-85° C., and the reaction time is 9-11 hours.

[0012] Furthermore, the stirring time in step S2 is 2-4 hours, the washing step is washed with deionized water for 3-5 times, and the drying step is dried in a vacuum drying oven at 90-110° C. for 4-5 hours.

[0013] Furthermore, in step S3, the raw materials of the high borosilicate glass include, by weight:

[0014] 68-72 parts of silicon dioxide, 20-23 parts of boron oxide, 2-4 parts of zinc oxide, 2-5 parts of sodium oxide, 1.2-1.5 parts of aluminum oxide and 0.1-0.3 parts of lithium oxide, and 0.3-0.5 parts of the microspheres obtained in step S2.

[0015] Furthermore, in step S3, after the melting is mixed and maintained at 1100-1140°C for 4-6 hours, the temperature is raised to 1395-1415°C at a rate of 0.4-0.8°C / min for melting; the clarification time is 30-40 hours, the blowing temperature is 1100-1140°C, the annealing temperature is 540-560°C, and the annealing time is 2-3 hours.

[0016] Furthermore, in step S1, the molar ratio of tetraethoxysilane to methyltrimethoxysilane is 1.5-1.7:1.

[0017] The present application also provides a low expansion coefficient high borosilicate glass, which is prepared according to the above-mentioned preparation method of the low expansion coefficient high borosilicate glass.

[0018] The beneficial effects of this application are:

[0019] By introducing octadecane-coated silica microspheres into the raw material of high borosilicate glass, the phase change characteristics of octadecane are used to adjust the thermal expansion behavior of the glass. This design makes the thermal expansion coefficient of the resulting high borosilicate glass significantly lower than that of traditional high borosilicate glass, showing great advantages. This shows that the glass produced by this method is less likely to crack under temperature changes and has stronger thermal stability. Despite the addition of phase change microspheres, the mechanical properties and optical uniformity of the glass are not affected or even improved by precisely controlling the size and doping ratio of the microspheres and strictly following a specific preparation process. The lower thermal expansion coefficient combined with the optimized glass matrix formula significantly improves the thermal shock resistance of the material and extends the service life of the product, which is of great significance for application scenarios that need to withstand sudden temperature changes, such as laboratory equipment, solar panel packaging, and kitchen heat-resistant appliances.

[0020] Through strict process control, such as the setting of melting temperature, clarification time, molding temperature and annealing conditions, not only the production efficiency is improved, but also the internal stress of the glass is effectively eliminated. By selecting a milder melting temperature, the uniform dispersion of silica microspheres in the glass is guaranteed. The performance of the final product is more excellent, meeting the stringent requirements of high-end application fields for material performance.

[0021] By adjusting the basic formula of high borosilicate glass, the ratio of boron oxide and silicon dioxide and adding specific amounts of other oxides, the thermal expansion coefficient of the glass is significantly reduced, the thermal shock resistance of the material is improved and the service life is extended. DETAILED DESCRIPTION

[0022] The technical scheme of the present invention and its effects are further described below by specific examples. The following examples are only used to illustrate the content of the present invention and are not used to limit the protection scope of the present invention. Simple changes made to the present invention by applying the concept of the present invention are all within the scope of the protection claimed by the present invention.

[0023] The equipment used in the preparation method of the present invention can be the well-known equipment in the art. The raw materials used in the present invention are commercially available unless otherwise specified.

[0024] Example 1

[0025] S1. Add 1.5 mL of tetraethoxysilane and 1.0 mL of methyltrimethoxysilane to 10 mL of deionized water, and heat to 75 °C for 11 h under stirring;

[0026] S2. After the reaction is finished and cooled, 0.14 g of octadecane and 0.014 g of 3-aminopropyltriethoxysilane are added and mixed evenly, and then 0.14 g of polyvinyl alcohol is added to the mixture, and after mixing evenly, 10 mL of 28% ammonium hydroxide aqueous solution is added dropwise, and stirring is continued at room temperature for 2 h. After filtering, the mixture is washed with deionized water for 3 times, and dried in a vacuum drying oven at 110 ° C for 4 h to obtain microspheres;

[0027] S3. After mixing, the raw materials of high borosilicate glass are melted at 1100°C for 6 hours, and then the temperature is raised to 1395°C at a rate of 0.4°C / min for melting until the raw materials are completely melted to form glass liquid. The mixture is clarified for 30 hours, blown at 1140°C, and annealed at 540°C for 2 hours to obtain the high borosilicate glass. The raw materials of the high borosilicate glass include, by weight, 65 parts of silicon dioxide, 20 parts of boron oxide, 2 parts of zinc oxide, 2 parts of sodium oxide, 1.2 parts of aluminum oxide, 0.1 parts of lithium oxide, and 0.2 parts of the microspheres obtained in step S2.

[0028] Example 2

[0029] S1. Add 2 mL of tetraethoxysilane and 0.75 mL of methyltrimethoxysilane to 10 mL of deionized water, and heat to 85 °C for 9 h under stirring;

[0030] S2. After the reaction is finished and cooled, 0.94 g of octadecane and 0.07 g of 3-aminopropyltriethoxysilane are added and mixed evenly, and then 0.18 g of polyvinyl alcohol is added to the mixture, and after mixing evenly, 10 mL of 28% ammonium hydroxide aqueous solution is added dropwise, and stirring is continued at room temperature for 4 h. After filtering, the mixture is washed with deionized water for 3 times, and dried in a vacuum drying oven at 90 ° C for 5 h to obtain microspheres;

[0031] S3. After mixing, the raw materials of high borosilicate glass are melted. After mixing and maintaining at 1140°C for 4 hours, the temperature is raised to 1415°C at a rate of 0.8°C / min for melting until the raw materials are completely melted to form glass liquid. The mixture is clarified for 40 hours, blown at 1120°C, annealed at 560°C, and the annealing time is 3 hours to obtain the high borosilicate glass. The raw materials of the high borosilicate glass include, by weight, 75 parts of silicon dioxide, 25 parts of boron oxide, 5 parts of zinc oxide, 5 parts of sodium oxide, 2 parts of aluminum oxide, 0.5 parts of lithium oxide, and 0.6 parts of the microspheres obtained in step S2.

[0032] Example 3

[0033] S1. Add 1.5 mL of tetraethoxysilane and 0.8 mL of methyltrimethoxysilane to 10 mL of deionized water, and heat to 85°C for 9 hours under stirring;

[0034] S2. After the reaction is finished and cooled, 0.42 g of octadecane and 0.02 g of 3-aminopropyltriethoxysilane are added and mixed evenly, and then 0.11 g of polyvinyl alcohol is added to the mixture, and after mixing evenly, 10 mL of 28% ammonium hydroxide aqueous solution is added dropwise, and stirring is continued at room temperature for 4 h. After filtering, the mixture is washed with deionized water for 3 times, and dried in a vacuum drying oven at 90 ° C for 5 h to obtain microspheres;

[0035] S3. After mixing, the raw materials of high borosilicate glass are melted. After mixing and maintaining at 1120°C for 5 hours, the temperature is raised to 1400°C at a rate of 0.6°C / min for melting until the raw materials are completely melted to form glass liquid. The mixture is clarified for 40 hours, blown at 1100°C, annealed at 550°C, and the annealing time is 3 hours to obtain the high borosilicate glass. The raw materials of the high borosilicate glass include, by weight: 68 parts of silicon dioxide, 23 parts of boron oxide, 4 parts of zinc oxide, 2 parts of sodium oxide, 1.5 parts of aluminum oxide, 0.3 parts of lithium oxide, and 0.5 parts of the microspheres obtained in step S2.

[0036] Example 4

[0037] S1. Add 1.5 mL of tetraethoxysilane and 0.8 mL of methyltrimethoxysilane to 10 mL of deionized water, and heat to 85°C for 9 hours under stirring;

[0038] S2. After the reaction is finished and cooled, 0.42 g of octadecane and 0.02 g of 3-aminopropyltriethoxysilane are added and mixed evenly, and then 0.11 g of polyvinyl alcohol is added to the mixture, and after mixing evenly, 10 mL of 28% ammonium hydroxide aqueous solution is added dropwise, and stirring is continued at room temperature for 4 h. After filtering, the mixture is washed with deionized water for 3 times, and dried in a vacuum drying oven at 100 ° C for 5 h to obtain microspheres;

[0039] S3. After mixing, the raw materials of high borosilicate glass are melted. After mixing and maintaining at 1100°C for 6 hours, the temperature is raised to 1395°C at a rate of 0.5°C / min for melting until the raw materials are completely melted to form glass liquid. The mixture is clarified for 40 hours, blown at 1150°C, annealed at 540°C, and the annealing time is 3 hours to obtain the high borosilicate glass. The raw materials of the high borosilicate glass include, by weight, 72 parts of silicon dioxide, 20 parts of boron oxide, 2 parts of zinc oxide, 5 parts of sodium oxide, 1.2 parts of aluminum oxide, 0.1 parts of lithium oxide, and 0.3 parts of the microspheres obtained in step S2.

[0040] Comparative Example 1

[0041] S1. Add 1.5 mL of tetraethoxysilane and 0.8 mL of methyltrimethoxysilane to 10 mL of deionized water, and heat to 85 °C for 9 h under stirring;

[0042] S2. After the reaction is finished and cooled, 0.42 g of octadecane and 0.02 g of 3-aminopropyltriethoxysilane are added and mixed evenly, and then 0.11 g of polyvinyl alcohol is added to the mixture, and after mixing evenly, 10 mL of 28% ammonium hydroxide aqueous solution is added dropwise, and stirring is continued at room temperature for 4 h. After filtering, the mixture is washed with deionized water for 3 times, and dried in a vacuum drying oven at 90 ° C for 5 h to obtain microspheres;

[0043] S3. After mixing, the raw materials of high borosilicate glass are melted. After mixing and maintaining at 1120°C for 5 hours, the temperature is raised to 1400°C at a rate of 0.6°C / min for melting until the raw materials are completely melted to form glass liquid. The mixture is clarified for 40 hours, blown at 1100°C, annealed at 550°C, and the annealing time is 3 hours to obtain the high borosilicate glass. The raw materials of the high borosilicate glass include, by weight: 68 parts of silicon dioxide, 23 parts of boron oxide, 4 parts of zinc oxide, 2 parts of sodium oxide, 1.5 parts of aluminum oxide, 0.3 parts of lithium oxide, and 2 parts of the microspheres obtained in step S2.

[0044] Comparative Example 2

[0045] S1. Add 1.5 mL of tetraethoxysilane and 1.5 mL of methyltrimethoxysilane to 10 mL of deionized water, and heat to 85 °C for 9 h under stirring;

[0046] S2. After the reaction is finished and cooled, 0.42 g of octadecane and 0.02 g of 3-aminopropyltriethoxysilane are added and mixed evenly, and then 0.11 g of polyvinyl alcohol is added to the mixture, and after mixing evenly, 10 mL of 28% ammonium hydroxide aqueous solution is added dropwise, and stirring is continued at room temperature for 4 h. After filtering, the mixture is washed with deionized water for 3 times, and dried in a vacuum drying oven at 90 ° C for 5 h to obtain microspheres;

[0047] S3. After mixing, the raw materials of high borosilicate glass are melted. After mixing and maintaining at 1120°C for 5 hours, the temperature is raised to 1400°C at a rate of 0.6°C / min for melting until the raw materials are completely melted to form glass liquid. The mixture is clarified for 40 hours, blown at 1100°C, annealed at 550°C, and the annealing time is 3 hours to obtain the high borosilicate glass. The raw materials of the high borosilicate glass include, by weight: 68 parts of silicon dioxide, 23 parts of boron oxide, 4 parts of zinc oxide, 2 parts of sodium oxide, 1.5 parts of aluminum oxide, 0.3 parts of lithium oxide, and 0.5 parts of the microspheres obtained in step S2.

[0048] Comparative Example 3

[0049] The raw materials of borosilicate glass are melted after mixing. After mixing and maintaining at 1120°C for 5 hours, the temperature is raised to 1400°C at a rate of 0.6°C / min for melting until the raw materials are completely melted to form glass liquid. The mixture is clarified for 40 hours, blown at 1100°C, annealed at 550°C, and the annealing time is 3 hours to obtain the high borosilicate glass. The raw materials of the high borosilicate glass include, by weight, 68 parts of silicon dioxide, 23 parts of boron oxide, 4 parts of zinc oxide, 2 parts of sodium oxide, 1.5 parts of aluminum oxide, and 0.3 parts of lithium oxide.

[0050] Comparative Example 4

[0051] S1. Add 1.5 mL of tetraethoxysilane and 0.8 mL of methyltrimethoxysilane to 10 mL of deionized water, and heat to 85 °C for 9 h under stirring;

[0052] S2. After the reaction is finished and cooled, 0.42 g of octadecane and 0.02 g of 3-aminopropyltriethoxysilane are added and mixed evenly, and then 0.11 g of polyvinyl alcohol is added to the mixture, and after mixing evenly, 10 mL of 28% ammonium hydroxide aqueous solution is added dropwise, and stirring is continued at room temperature for 4 h. After filtering, the mixture is washed with deionized water for 3 times, and dried in a vacuum drying oven at 90 ° C for 5 h to obtain microspheres;

[0053] S3. After mixing, the raw materials of high borosilicate glass are melted at 1415° C. until the raw materials are completely melted to form glass liquid, clarified for 40 hours, blown at 1100° C., annealed at 550° C. for 3 hours to obtain the high borosilicate glass. The raw materials of the high borosilicate glass include, by weight: 68 parts of silicon dioxide, 23 parts of boron oxide, 4 parts of zinc oxide, 2 parts of sodium oxide, 1.5 parts of aluminum oxide, 0.3 parts of lithium oxide, and 0.5 parts of the microspheres obtained in step S2.

[0054] The samples obtained from Examples 1-4 and Comparative Examples 1-4 were subjected to performance tests, and the test results are shown in the following table.

[0055]

[0056] Optical uniformity is tested according to GB / T7962.3-2010, expansion coefficient is tested according to GB / T7962.16-2010, and surface hardness parameters are measured by GB / T6739-1996 method. Thermal shock resistance is tested according to GB / T4547-2007, the glass is placed in a 480℃~500℃ high temperature furnace for 5 minutes, then taken out and placed in 15℃~25℃ water for cooling, and the number of cracks is repeated and recorded.

Claims

1. A method for preparing low expansion coefficient high borosilicate glass, characterized in that The following steps are involved: S1, adding tetraethoxysilane and methyltrimethoxysilane into deionized water, heating and reacting under stirring, wherein the molar ratio of tetraethoxysilane to methyltrimethoxysilane is 1-1.8:1; S2. After the reaction is finished and cooled, octadecane and 3-aminopropyltriethoxysilane are added and mixed evenly, and then polyvinyl alcohol is added to the mixture. After mixing evenly, an aqueous solution of ammonium hydroxide is added dropwise, and stirring is continued at room temperature. After filtering, washing and drying are performed to obtain microspheres, wherein the mass ratio of octadecane, tetraethoxysilane, 3-aminopropyltriethoxysilane and polyvinyl alcohol is 0.1-0.5:1:0.01-0.04:0.05-0.1; S3. After mixing, the raw materials of high borosilicate glass are melted until the raw materials are completely melted to form glass liquid. After clarifying and blowing annealing, the high borosilicate glass is obtained. The raw materials of the high borosilicate glass include, by weight: 65-75 parts of silicon dioxide, 20-25 parts of boron oxide, 2-5 parts of zinc oxide, 2-5 parts of sodium oxide, 1.2-2 parts of aluminum oxide, 0.1-0.5 parts of lithium oxide, and 0.2-0.6 parts of the microspheres obtained in step S2.

2. The method for preparing low expansion coefficient high borosilicate glass according to claim 1, characterized in that: The heating temperature in step S1 is 75-85° C. and the reaction time is 9-11 hours.

3. The method for preparing low expansion coefficient high borosilicate glass according to claim 1, characterized in that: The stirring time in step S2 is 2-4 hours, the washing step is washed with deionized water for 3-5 times, and the drying step is dried in a vacuum drying oven at 90-110° C. for 4-5 hours.

4. The method for preparing low expansion coefficient high borosilicate glass according to claim 1, characterized in that: In step S3, the raw materials of the high borosilicate glass include, by weight: 68-72 parts of silicon dioxide, 20-23 parts of boron oxide, 2-4 parts of zinc oxide, 2-5 parts of sodium oxide, 1.2-1.5 parts of aluminum oxide and 0.1-0.3 parts of lithium oxide, and 0.3-0.5 parts of the microspheres obtained in step S2.

5. The method for preparing low expansion coefficient high borosilicate glass according to claim 1, characterized in that: In step S3, the mixture is melted at 1100-1140°C and kept for 4-6 hours, and then the temperature is raised to 1395-1415°C at a rate of 0.4-0.8°C / min for melting; the clarification time is 30-40 hours, the blowing temperature is 1100-1140°C, the annealing temperature is 540-560°C, and the annealing time is 2-3 hours.

6. The method for preparing low expansion coefficient high borosilicate glass according to claim 1, characterized in that: The molar ratio of tetraethoxysilane to methyltrimethoxysilane in step S1 is 1.5-1.7:

1.

7. A low expansion coefficient high borosilicate glass, characterized in that The glass is prepared according to the method for preparing low expansion coefficient high borosilicate glass according to any one of claims 1 to 6.

Citation Information

Patent Citations

  • A method for preparing high borosilicate glass, high borosilicate glass and its applications

    CN103626395B

  • High-temperature-resistant low-expansion ceramic glaze, preparation method thereof and ceramic product

    CN112047629A

  • High borosilicate glass as well as preparation method and application thereof

    CN116002973A

  • Rapid synthesis method of nanometer phase change microcapsule packaged by silicon dioxide

    CN117801790A